Evaluation the Effect of Residual Stress on Fracture of Polyethylene Pipe under Pressure Loading - Jasim, Haider Hadi (Basrah Journal for Engineering Sciences, 2016)
In this paper, the Weibull uni-axial and multi-axial distribution function for polyethylene pips under pressure loading were developed and analyzed taking account of residual stress. Tensile test was achieved to determine mechanical properties and the Weibull parameters. Experimental method using the hole- drilling strain-gage method was used to measure the residual stresses in PE pipe and compare with that obtained from numerical finite element method (FEM). The obtained results show that there is a convergence between uni-axial and multi-axial distribution function, but multi-axial distribution function give large values compared to uni-axial distribution function. It was observed that the residual stresses have influence on failure assessment diagram and causes translation from elastic-plastic failure to brittle failure.